2011
DOI: 10.2478/v10153-010-0036-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum inflammatory cytokines IL-1β, IL-6, TNF-α and VEGF have influence on the development of diabetic retinopathy

Abstract: AIm: The aim of this study was to analyze the correlation between serum levels of inflammatory cytokines Il-1β, Il-6, TnF-α and vegF and the presence and severity of diabetic retinopathy (dR) in patients with type 2 diabetes mellitus (dM). PAtIents And methods: In this prospective study we included 38 healthy volunteers (group 1) and 39 patients with type 2 dM (group 2). all participants underwent routine ophthalmological examination and laboratory analysis of the serum cytokines Il-1β, Il-6, TnF-α and vegF. g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(104 citation statements)
references
References 25 publications
6
96
1
1
Order By: Relevance
“…TNF-may become a relevant indicator of development and risk of diabetic retinopathy. Similar observations were made in adult patients with PDR (Gustavsson et al, 2008;Koleva-Georgieva et al, 2011). Levels of TNF-in vitreous of Type 2 diabetic patients with PDR were higher than those found in control group.…”
Section: Tumor Necrosis Factor Alpha (Tnf-α)supporting
confidence: 75%
See 1 more Smart Citation
“…TNF-may become a relevant indicator of development and risk of diabetic retinopathy. Similar observations were made in adult patients with PDR (Gustavsson et al, 2008;Koleva-Georgieva et al, 2011). Levels of TNF-in vitreous of Type 2 diabetic patients with PDR were higher than those found in control group.…”
Section: Tumor Necrosis Factor Alpha (Tnf-α)supporting
confidence: 75%
“…On the other hand M1 macrophages prevented neovascularisation within retina due to high secretion of IL-6, IL-12 and IL-23. Although, majority of reports confirm its negative role in the onset and progression of diabetic retinopathy (Noma et al, 2009;Funk M et al, 2010;Koleva-Georgieva et al, 2011). IL-6 is produced mainly by macrophages, monocytes, lymphocytes T and B, while in the eye IL-6 is produced by keratocytes, Müller cells, pigmented epithelium, corneal epithelium, iris and ciliary body (Yoshida et al, 2001).…”
Section: Interleukin 6 (Il-6)mentioning
confidence: 99%
“…Alternatively, TNF-α knockout may block DR progression by removing TNF-α from the bloodstream. It is feasible that TNF-α represents an external factor that promotes or aggravates retinal inflammation and vascular dysfunction in DR. Several clinical studies have found that average serum levels of TNF-α are increased in patients with PDR and correlate with other systemic indicators of inflammation [85,87,[149][150][151][152][153]. Relative to healthy controls, plasma levels of TNF-α progressively increase in diabetic patients with no retinopathy, with nonproliferative DR and with PDR [153].…”
Section: Additional Cytokines In Drmentioning
confidence: 99%
“…Disease processes which have been shown to increase vascularity include, in particular, endocrine glands illness [24,25], acromegaly [19], pituitary adenomas [26,27], autoimmune thyroid disease, goitre, neoplasms [18,22] and eye disorders -retinopathy occurring in premature infants [18,28], diabetic retinopathy [18,20,21,[29][30][31], uveitis and other ocular illnesses. Angiogenesis commonly occurs in inflammatory diseases [18-20, 22, 24-27].…”
Section: Introductionmentioning
confidence: 99%